Static Analysis for Dynamic XML - Christensen, Aske Simon; Møller, Anders; Schwartzbach, Michael I. (BRICS Report Series, 2002)
We describe the summary graph lattice for dataflow analysis of programs that dynamically construct XML documents. Summary graphs have successfully been used to provide static guarantees in the JWIG language for programming interactive Web services. In particular, the JWIG compiler is able to check validity of dynamically generated XHTML documents and to type check dynamic form data. In this paper we present summary graphs and indicate their applicability for various scenarios. We also show that summary graphs have exactly the same expressive power as the regular expression types from XDuce, but that the extra structure in summary graphs makes them more suitable for certain program analyses.